2014
DOI: 10.1111/jgs.13165
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Inflammation and Cognitive Function in African Americans and European Americans

Abstract: OBJECTIVES Elucidating associations of specific inflammatory biomarkers with cognitive function in African Americans (AA) and European Americans (EA) with prevalent vascular risk factors could identify vascular-mediated effects on cognitive impairment. DESIGN Cross-sectional analysis using Generalized Estimating Equations to account for familial clustering; standardized β-coefficients, adjusted for age, sex, and education are reported. SETTING A community cohort study in Jackson, MS and Rochester, MN. PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 54 publications
6
46
0
Order By: Relevance
“…Similarly, depression has been associated with systemic diseases involving induction of a pro-inflammatory state or upregulation of inflammatory markers. For example, levels of IL-6 have been found to increase with age (25) and be associated with cognitive wellbeing (26). In addition, depression caused an increase in fatty lesions in arteries in a mouse model, providing a potential link between psychological stress and vascular diseases (27).…”
Section: Central and Peripheral Markers Of Inflammation In Depressionmentioning
confidence: 99%
“…Similarly, depression has been associated with systemic diseases involving induction of a pro-inflammatory state or upregulation of inflammatory markers. For example, levels of IL-6 have been found to increase with age (25) and be associated with cognitive wellbeing (26). In addition, depression caused an increase in fatty lesions in arteries in a mouse model, providing a potential link between psychological stress and vascular diseases (27).…”
Section: Central and Peripheral Markers Of Inflammation In Depressionmentioning
confidence: 99%
“…To the Editor : In Dr. Naharci's thoughtful comments on our recent article in this journal, he suggested that frailty, depression, and medications for hypertension and diabetes mellitus could be important considerations in the relationship between inflammation and cognition. Dr. Naharci correctly noted that a significant proportion of the GENOA cohort were taking medications for hypertension and diabetes; 495 (18%) were taking medications for diabetes mellitus and 1,902 (70%) for hypertension.…”
Section: Standardized Relationships Between Cognitive Domains and Infmentioning
confidence: 99%
“…To the Editor : In a recent issue of the Journal of the American Geriatrics Society , Windham and colleagues reported interesting and valuable findings regarding the role of inflammation in cognitive dysfunction according to race . Although growing evidence indicates such a link, the important aspect of this study is that inflammatory markers (high‐sensitivity C‐reactive protein (CRP), interleukin (IL)‐6, soluble tumor necrosis factor (TNF) receptors) are differentially associated with cognitive domains in African Americans and European Americans with vascular risk factors . Several points merit discussion.…”
mentioning
confidence: 94%
“…As shown in Table 1, hypertension was present in nearly three quarters of participants, and one in five participants had diabetes mellitus, indicating that a significant proportion of the sample was receiving medications for two comorbidities. It has been reported that inflammation markers improved with antihypertensive and antidiabetic agents …”
mentioning
confidence: 99%